THE SPIRITUAL AND EDUCATIONAL OF THE NOVEL "LOLAZOR", ARTISTIC-AESTHETIC, PSYCHOLOGICAL FUNDAMENTALS - Berdiyeva Nazira Uralovna (Scholar Express Journal, 2023)
Literary heroes of MMDost cannot be compared to anything else in this respect. Literary heroes enter people's mind and thinking in various ways, that is, the reader is involuntarily influenced by literary heroes
Keywords: author's point of view; social; philosophical